Bionanocomposites based on a covalent network of chitosan and edge functionalized graphene layers - Vincenzina Barbera (SAGE Publishing, 2021)
In this study, carbon papers and aerogels were prepared from chitosan and graphene layers with aldehydic edge functional groups (G-CHO) able to form chemical bonds with chitosan and thus to form a crosslinked network. A high surface area graphite was edge functionalized with hydroxyl groups (G-OH) through the reaction with KOH. G-CHO, with 4.5 mmol/g of functional group, was prepared from G-OH by means of the Reimer-Tieman reaction. Characterization of the graphitic materials was performed with elemental analysis, titration, X-ray analysis, Raman spectroscopy and by estimating their Hansen solubility parameters. CS and G-CHO were mixed with mortar and pestle and carbon papers and aerogels were obtained from a stable acidic water suspension through casting and liophilization, respectively. Free standing and foldable carbon papers and monolithic aerogels based on a continuous covalent network between G-CHO and CS were prepared. G-CHO, which had about 22 stacked layers, was extensively exfoliated in the carbon paper, as confirmed by the absence of the 002 reflection of the graphitic crystallites in the XRD pattern. Carbon paper was found to be resistant to solvents and to be stable for pH ⩾ 7. Composites revealed electrical conductivity. The covalent network between the graphene layers and CS, suggested by the IR findings, accounts for these results. This work demonstrates the effectiveness of a continuous covalent network between chitosan and graphene layers edge functionalized with tailor made functional groups for the preparation of carbon papers and aerogels and paves the way for the scale up of such a type of composites.